Goal-directed hemodynamic therapy in patients with colorectal cancer undergoing laparoscopic surgery - V. A. Panaﬁdina; I. V. Shlyk (Вестник анестезиологии и реаниматологии, 2020)
Introduction. The conductance of goal-directed hemodynamic therapy is controversial due to the difficulty in its implementation in routine practice despite the signiﬁcant number of studies and meta-analyses.Objective. To estimate the efficacy of a modiﬁed algorithm of goal-directed hemodynamic management in patients with colorectal cancer who undergo laparoscopic surgery based on non-invasive monitoring of cardiac output.Subjects and methods. A single-centered, randomized trial was conducted. The control group included 75 patients, while the goal-directed therapy (GDT) group included 72 patients. In the control group, hemodynamic management was based on mean arterial pressure and intraabdominal perfusion pressure. In addition, results of ﬂuid responsiveness tests were considered in the GDT group. The suggested protocol efficacy was evaluated on the basis of frequency of critical incidents, shifts in acid-base balance and lactate concentration, infusion volume, vasopressor doses, the incidence of acute kidney injury, and other complications.Results. After anesthesia induction and according to the results of a modiﬁed, passive leg raising test, 67.1% of patients were considered responders and received 1250 (1000; 1500) ml of balanced crystalloids before carboxyperitoneum. The infusion differentiation test of hypotension cause was performed in 47 patients of the GDT group, 37% were considered responders, and others received vasopressors and/or inotropes. The use of the GDT protocol led to a decrease in total infusion volume and vasopressor doses. A lower frequency of critical incidents was recorded when the GDT protocol was used. In the GDT group, there were no signs of ischemia and increased frequency of complications (including acute kidney injury).Conclusions. Testing of ﬂuid responsiveness and non-invasive cardiac output monitoring allows for the correction of hemodynamics during surgery. Goal-directed therapy in the intraoperative period allows different approaches to maintaining systemic and intraabdominal perfusion pressure, thus decreasing the total volume of infusion without increasing hypoperfusion risk.